2009
DOI: 10.1002/ana.21745
|View full text |Cite
|
Sign up to set email alerts
|

Human neural stem cells ameliorate autoimmune encephalomyelitis in non‐human primates

Abstract: Herein, we provide the first evidence that human CNS stem cells ameliorate EAE in nonhuman primates without overt side effects. Immune regulation (rather than neural differentiation) is suggested as the major putative mechanism by which NPCs ameliorate EAE in vivo. Our findings represent a critical step toward the clinical use of human NPCs in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(200 citation statements)
references
References 42 publications
11
189
0
Order By: Relevance
“…NPC transplantation in MOG35-55-induced EAE mice attenuated brain inflammation, reduced acute and chronic axonal injury and demyelination, and improved the overall clinical and neurophysiological performance of the CNS of the mice [173,174]. Finally, such immune regulatory properties were also shown for human embryonic-stem cellderived NPCs in rodents [151] and for somatic NPCs in primates [175]. Again, the therapeutic effects of both these latter NPC sources was not related to graft-or host-driven remyelination, but rather were mediated by an immune regulatory mechanism that protected the CNS from immunemediated injury [151].…”
Section: Immune Modulationmentioning
confidence: 81%
“…NPC transplantation in MOG35-55-induced EAE mice attenuated brain inflammation, reduced acute and chronic axonal injury and demyelination, and improved the overall clinical and neurophysiological performance of the CNS of the mice [173,174]. Finally, such immune regulatory properties were also shown for human embryonic-stem cellderived NPCs in rodents [151] and for somatic NPCs in primates [175]. Again, the therapeutic effects of both these latter NPC sources was not related to graft-or host-driven remyelination, but rather were mediated by an immune regulatory mechanism that protected the CNS from immunemediated injury [151].…”
Section: Immune Modulationmentioning
confidence: 81%
“…In vitro, both MSCs and NPCs are MHC-I low/medium and MHC-II negative (Klyushnenkova et al, 2005;Le Blanc et al, 2003;Pluchino et al, 2005Pluchino et al, , 2009a, but upregulation of MHC-I and -II expression is observed after long-term neurosphere expansion (Laguna Goya et al, 2011;Odeberg et al, 2005) or NPC exposure to proinflammatory cytokines such as interferon (IFN)-γ or tumor necrosis factor (TNF)-α (Johansson et al, 2008). Under basal growth conditions the co-stimulatory molecules CD80/ B7.1, CD86/B7.2 and CD40 are also absent in both MSCs and NPCs (Odeberg et al, 2005;Tse et al, 2003).…”
Section: In Vitro Stem Cell Immunogenicitymentioning
confidence: 99%
“…Human NPCs suppress the proliferation and alter the cytokine secretion profiles of xenogeneic (e.g. marmoset), antigen-specific and allogeneic mitogen-activated T cells (Kim et al, 2009b;Pluchino et al, 2009a). Compared with rodent NPCs, human NPCs have a lower cytotoxicity towards T cells, but a higher cytotoxicity toward monocyte/macrophages (Ricci-Vitiani et al, 2007) in vitro.…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…38 In Coronel et al's study it is likely that the grafted MSCs exerted anti-nociceptive effects by either preventing injury-induced galanin upregulation with stimulation of pre-synaptic GAL2 receptors on primary afferents, or alternatively, stimulating GAL1 receptors. Other evidence supportive of the reparative immunological mechanisms in Franchi et al's study have shown that: the efficacy of transplanted NSCs in the treatment of neuropathic pain is mediated via neuroprotective and immunomodulatory mechanisms; 39 and that in a mouse model of spared nerve injury, intra-ventricular injection of human MSCs decreased mRNA levels of the proinflammatory IL-1 gene and suppressed activation of astrocytes and microglia, which was associated with a reduction in painlike behaviours. 40 The utility of intravenous systemic NSC administration in the treatment of neuropathic pain is further corroborated by evidence on the physiological mechanisms underlying NSC migration, namely, that NSCs cross the blood-brain barrier and enter the CNS where they modulate pain.…”
Section: Evidence On the Utility Of Adult Stem Cells For The Treatmenmentioning
confidence: 87%